A retrospective study of the ethnic identity development in the childhood: Analysis of ethnic autobiographies of high school students - Gritsenko, Valentina V.; Murashcenkova, Nadezhda V.; Efremenkova, Maria N. (Известия Саратовского университета. Новая серия. Серия Акмеология образования: Психология развития, 2023)
The contradiction between the necessity to identify the resource potential of ethnic identity in modern conditions, on the one hand, and the contradictory data on its development in persons whose socialization takes place in an ethnically homogeneous environment, on the other hand, makes the study issue relevant. The research purpose: a retrospective study of the ethnic identity development in high school students living in a mono-ethnic Russian region – the Smolensk region. Research questions: At what age do children living in a mono-ethnic environment acquire the fi rst information about their own and other ethnic groups? How do children feel about their ethnic group in the process of identifying with it? What is the role of the family in shaping the ethnic identity of children? The study participants are 185 secondary school students from Smolensk who identify themselves as Russians, aged from 15 to 18; the average age is 16.3 years old; 59.5% of them are females. The research methods (tools) used: the technique “Ethnic autobiography” (by P. V. Rumyantseva), aimed at studying the development of ethnic identity in the childhood. The processing of the research results was carried out with the help of frequency and content analysis methods. The research results: most of the students acquired their fi rst knowledge of Russian and other ethnic groups at preschool and primary school age and experienced positive feelings about their ethnicity. A third of the high school students showed an indiff erent attitude to their ethnicity. The contribution of the family to the ethnic identity development weakens in a situation where parents belong to diff erent nationalities or when the children do not know their parents’ nationality. The main conclusions. Development of the ethnic identity of the majority of high school students, who live in a mono-ethnic Russian environment, takes place in the process of family upbringing, it is smooth, without any shocks and changes, it is characterized by a positive attitude towards their belonging to the Russian ethnic group. The indiff erent attitude of some high school students to their ethnicity may, on the one hand, indicate its irrelevance and insignifi cance for children living in a mono–ethnic environment, and on the other hand, it can be considered as an indicator of a “hidden” identity that can be actualized under certain conditions. The research fi ndings should be taken into account in order to increase the eff ectiveness of intercultural interaction and to develop national civil Russian consolidation.